Writing the Public Administration Academic Articles for Publishinng - Tossamas, Pattarapon; Wichairum, Stapron; Jhogmeesook, Thanaphat (Journal for Developing the Social and Community, 2017)
This article aims to present techniques and method for writing the academic article qualitively in order to be published in academic journal, thus, academician need to have knowledges, abilities including skills such as phenomenon study, logical thinking, in-depth interviews, relevant literature review, verifying the credibility of article content by integration method, phenomenal forecasting bu inductive and deductive. In other hand, the composition of academic articles consists of: (1) Introduction; title,